Does Fiscal Decentralization Improve Social Welfare? Evidence From Indonesian Provinces - Fitri S Kasim; Busman Busman; Zulfikar Jakaputera Djalamang (Jurnal Riset Ilmu Ekonomi, 2026)
This study examines the relationship between fiscal decentralization and community welfare in Indonesia by testing the mediating role of economic growth. Using panel data from 34 provinces during 2020–2024, the study applies a formative Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach to evaluate both direct and indirect structural relationships. Fiscal decentralization is represented by local own-source revenue, capital expenditure, and intergovernmental transfers, while welfare is measured through poverty, real per capita expenditure, life expectancy, and income inequality indicators. The findings reveal that fiscal decentralization has a significant positive direct effect on community welfare, indicating that regional fiscal capacity contributes substantially to improving social outcomes across provinces. However, economic growth does not function as a significant mediating variable, as the indirect effect is statistically insignificant and the predictive relevance of the growth construct remains weak. These results suggest that the effectiveness of fiscal decentralization in Indonesia is driven more by the quality and orientation of public expenditure toward social sectors than by aggregate economic expansion. The study contributes to the fiscal decentralization literature by emphasizing the importance of outcome-based welfare approaches in evaluating regional fiscal performance. Policy implications highlight the need to strengthen welfare-oriented fiscal allocation frameworks to support more inclusive and equitable regional development in Indonesia.